Penyusunan Instrumen Pengukuran Ikhlas - Lu'luatul Chizanah; M. Noor Rochman Hadjam (Psikologika: Jurnal Pemikiran dan Penelitian Psikologi, 2013)
Ikhlas as a psychological construct does not have any instrument. Based on that fact, the research is aimed at developing a instrument so the topic of ikhlas can be developed more widely. The process of preparation carried out in three stages, namely (1) writing items of ikhlas' scale, (2) content validation through professional judgment and cognitive debriefing, and (3) testing the reliability with alpha-cronbach approach. The subjects in this study amounted to 224 people. The result of this research was a ikhlas' scale consist of 22 items. The reliability's score of scale was 0,809. It shows that the scale developed can be considered as a good instrument of ikhlas.Keywords: ikhlas' scale, cognitive debriefing, content validation